COMMUNITY PARTICIPATION IN NATURE TOURISM DEVELOPMENT: LESSONS FROM PINDUL CAVE IN YOGYAKARTA, INDONESIA - Musadad Musadad (Universitas Gadjah Mada, 2018)
Local community's participation is essential for a tourism development, especially in a nature tourism destination like Pindul Cave in Gunungkidul Regency, Yogyakarta. In addition to contributing to the sustainability of the nature tourism itself, community participation can empower the local community since they are usually benefited from the tourism activities running in their area. Therefore, this study seeks to identify the level of community participation in nature-based tourism development and barriers to the community participation. This study employed a descriptive quantitative approach. The data was collected by randomly distributing questionnaires to 60 residents and conducting interviews with the locals and village tourism managers. The results suggested that the level of community participation is averagely high in terms of age, gender, job, income, and education. Nevertheless, their participation level is low in the evaluation so there should be a monitoring team to handle this issue. In addition, the local community still faces several barriers to participation, including incompetency of tourism industry, poverty, management's policy, and lack of ability to speak English. Therefore, there should be advocating programs to overcome these problems.